Archaeometallurgical Analyses on Two Renaissance Swords from the “Luigi Marzoli” Museum in Brescia: Manufacturing and Provenance - Carolina Mori; Giorgia Ghiara; Paolo De Montis; Paolo Piccardo; Giacomo D. Gatta; Stefano Pierpaolo Trasatti (Heritage, 2021)
Two Venetian types of swords coming from the “Luigi Marzoli” Arms Museum in Brescia were characterized in this study, to understand their manufacturing process and to gather information about their provenance. Both the blades and the hilts components are analyzed using a multi-methodological approach, to describe possible differences in the metallurgical features that involved classical metallographic and spectroscopic techniques. Microstructural results indicate a complex process for the manufacturing of the blades, by hot-forging, confirmed by a sequence of different microstructures even on the same sample. Furthermore, an interesting and unusual manufacturing technique is used on one of the pommels, which consists of two hemispheres connected by copper joints. Hypothesis about the ironmaking and the provenience of raw materials are obtained by the features and composition of the inclusions. It is suggested that there is the use of both a direct and an indirect process on the swords. It is likely that the minerals used to obtain iron and copper of the swords come from the mines of the Brescia and Bergamo territories. All the hypotheses are consistent with the historical documents of the time that also give information on the diffusion of such swords in the Brescia area.